2016
DOI: 10.1017/s0029665116000306
|View full text |Cite
|
Sign up to set email alerts
|

Chrono-nutrition: a review of current evidence from observational studies on global trends in time-of-day of energy intake and its association with obesity

Abstract: The importance of the circadian rhythm in regulating human food intake behaviour and metabolism has long been recognised. However, little is known as to how energy intake is distributed over the day in existing populations, and its potential association with obesity. The present review describes global trends in time-of-day of energy intake in the general population based on data from cross-sectional surveys and longitudinal cohorts. Evidence of the association between time-of-day of energy intake and obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(143 citation statements)
references
References 58 publications
5
128
1
2
Order By: Relevance
“…This change is likely instigated by the reduction in stored fat that occurs through the decreased food intake. Although the role that the circadian rhythm plays in food intake behavior and in maintaining metabolism is widely recognized (Almoosawi et al, 2016), the mechanisms by which green tea regulates food intake do not seem to be governed by circadian rhythms: in the current study, all groups exhibited lower food intake, regardless of the type of diet or the time at which green tea was consumed.…”
Section: Evaluation Of the General Physiological Parameterscontrasting
confidence: 54%
“…This change is likely instigated by the reduction in stored fat that occurs through the decreased food intake. Although the role that the circadian rhythm plays in food intake behavior and in maintaining metabolism is widely recognized (Almoosawi et al, 2016), the mechanisms by which green tea regulates food intake do not seem to be governed by circadian rhythms: in the current study, all groups exhibited lower food intake, regardless of the type of diet or the time at which green tea was consumed.…”
Section: Evaluation Of the General Physiological Parameterscontrasting
confidence: 54%
“…Existing research examining patterning of EOs is diverse, and covers a range of concepts including EO frequency and spacing, meal regularity, timing and skipping or temporal eating patterns [2]. “Temporal eating patterns” refers to the timing, frequency and regularity of food intake or EOs across the day [4]. This emerging field of research on the timing of food intake is known as “chrono-nutrition [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence to suggest that weight gain in shift workers may be related to poor diet quality (8,9). However, little research has examined temporal eating patterns in relation to dietary intakes and health outcomes in non-shift-work populations (10). Several epidemiologic studies have reported a positive association between evening energy intakes (EIs) and daily total EIs (11,12) and obesity (10,13).…”
Section: Introductionmentioning
confidence: 99%
“…However, little research has examined temporal eating patterns in relation to dietary intakes and health outcomes in non-shift-work populations (10). Several epidemiologic studies have reported a positive association between evening energy intakes (EIs) and daily total EIs (11,12) and obesity (10,13). The later timing of an EO has also been associated with higher total EIs (14) and less successful weight loss (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation